The Effect of Turkey's Urbanization Process on The Models of Housing Prodiction - Akgün, Asiye Gültekin (My University, 2017)
Transformation of city in the industrialized country has effected the development of delayed and problematic urbanization in the non-industrialized country. The cities that have not evolved their own social integrity have taken the changes that was imposed by industrialized cities without any filter. With this effect, non-equal spaces have emerged in the organically growing cities. From the 19th century Ottoman period, the similar spatial transformations are also seen in Turkey’s urbanization process. Today, from the late Ottoman time, urbanization policies can be considered as part of the construction of social and political modernization project. This study, at first, focused on the urbanization process in terms of the discourses and practices of political actors in four periods and the relations of actors emerging during these periods. After that, the evoluation of the housing production model in these periods is explained. It can be said that there is a change in the perception of recent housing concept by the changing consumption habits and life style. Literature review and observation were carried out as the method of the study.
Keywords: Modernizasyon Projesi; Ekonomi-Politik; Kentleşme; Konut Üretim Modeli; Modernization Project; Economy-Politic; Urbanization; Housing Production Model